GLP-1 receptor agonists - Arbañil- Huamán, Hugo César (2020)
The evolution and discovery of a molecule derived from the proglucagon with incretinic effect is described. In the search for a molecule resistant to the rapid metabolism caused by DPP-4, it was found molecules such as Exendin 4 and subsequently the synthetic ones, specific to the GLP-1 receptor and resistant to the metabolism of DPP-4. It was also found that they had cardiovascular and renal advantages in the safety studies before their were approved, in particular the longacting and parenteral ones but not those of oral absorption.